THE INTERNET - Payne, Frances; Lindsell, Marianne; Redback Publishing (Frenchs Forest, NSW : Redback Publishing, 2020)
With an emphasis on cybersecurity, this guide to the internet is aimed at children, but will also be a great introduction for anyone who wants to know what the world wide web is all about. Lots of useful tips on how to use the internet, keep safe and just enjoy browsing.
Includes index
Keywords: Internet -- Juvenile literature; World Wide Web -- Juvenile literature